2016
DOI: 10.1017/s1360674315000465
|View full text |Cite
|
Sign up to set email alerts
|

Old ‘truths’, new corpora: revisiting the word order of conjunct clauses in Old English

Abstract: In Bech (2001a, 2001b), I took issue with the oft-repeated claim that Old English conjunct main clauses are commonly verb-final, and disproved it. However, the myth persists. In the meantime, theYork–Toronto–Helsinki Parsed Corpus of Old English Prose(YCOE, Tayloret al.2003) has been created, so the time has come to revisit this topic and consider it in light of new, extensive and generally accessible data. Using the YCOE corpus, I confirm and expand on Bech's (2001a, 2001b) empirical findings, showing that (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 16 publications
(27 reference statements)
2
16
0
Order By: Relevance
“…According to Haeberli, the status of quotative inversion is not on a par with other V-2 clauses he analyses in his study because ‘[a]t the surface, [it] looks like a parenthetical V-1 clause rather than like a genuine example in which subject-verb inversion occurs due to the fronting of a non-operator’ (Haeberli 2002: 271). A similar view is expressed by Bech in the context of OE syntax: ‘It is therefore not obvious that the syntax of constructions containing direct speech has the integrated structure that enables syntactic-typological reasoning; it is closer to a text structure containing a sequence of two main clauses’ (Bech 2017: 12). Therefore, scholars working on OE usually regard clauses such as (13) as instances of the rare V-1 order (which is said to be particularly well attested in clauses with verbs of saying) (Calle-Martín & Miranda-García 2010; Mitchell 1985: §3930) and not as examples of V-2.…”
Section: Reporting Clauses and Quotative Inversionmentioning
confidence: 78%
“…According to Haeberli, the status of quotative inversion is not on a par with other V-2 clauses he analyses in his study because ‘[a]t the surface, [it] looks like a parenthetical V-1 clause rather than like a genuine example in which subject-verb inversion occurs due to the fronting of a non-operator’ (Haeberli 2002: 271). A similar view is expressed by Bech in the context of OE syntax: ‘It is therefore not obvious that the syntax of constructions containing direct speech has the integrated structure that enables syntactic-typological reasoning; it is closer to a text structure containing a sequence of two main clauses’ (Bech 2017: 12). Therefore, scholars working on OE usually regard clauses such as (13) as instances of the rare V-1 order (which is said to be particularly well attested in clauses with verbs of saying) (Calle-Martín & Miranda-García 2010; Mitchell 1985: §3930) and not as examples of V-2.…”
Section: Reporting Clauses and Quotative Inversionmentioning
confidence: 78%
“…The V-final order, defined as S…V with a heavy intervening element such as a nominal object, a nominal or adjectival complement, or a nonfinite verb form (Mitchell 1985:§3911), is rare in main clauses unless they are coordinated (that is, introduced by the coordinating conjunction and or ac ; Fischer et al 2000:53, Ringe & Taylor 2014:419). That said, however, some recent corpus studies of OE report that V-final coordinate clauses are not as common in OE as traditionally assumed (Cichosz et al 2016, Bech 2017). In noncoordinate main clauses, the frequency of the V-final order is “generally on the low side” (Ringe & Taylor 2014:406), but “is much higher than previously acknowledged” (Pintzuk & Haeberli 2008).…”
Section: V-final Order In Oe and The Presence Of Hwætmentioning
confidence: 89%
“…As discussed in section 2, it is not impossible to find V-final main clauses in OE, though it is a minority pattern, even in coordinate clauses (Cichosz et al 2016, Bech 2017). In this section, I show that the order in hwæt (þa) -clauses is influenced by the same factors that increase the use of the V-final order in main clauses.…”
Section: Alternative Analysis: Hwæt (þA)-clauses As Main Clausesmentioning
confidence: 99%
“…f) XSXV(X): a clause in which an element other than the subject is fronted, and it is immediately followed by an overt subject, with an intervening element between the subject and the finite verb, which does not have to be the last clause constituent (treated as a variant of V-final or V-late in Bech 2017);…”
Section: Methodsmentioning
confidence: 99%
“…Since it is reported that OE conjunct clauses differ from non-conjunct clauses in their clear preference for non-VS inversion (Bech 2017), it seems important to take a closer look at the impact of coordination on the constituent order of negated main clauses. Therefore, in section 5, presenting the general results, main clauses are divided into conjuncts and non-conjuncts.…”
Section: Verb-initial Declarative Clausesmentioning
confidence: 99%